YERSINIA PESTIS VOLE’S STRAINS: TAXONOMY, PHYLOGEOGRAPHY, POLYMORPHISMS OF PATHOGENICITY FACTORS AND SELECTIVE VIRULENCE - A. P. Anisimov; E. A. Krasil’nikova; A. S. Vagaiskaya; V. I. Solomentsev; P. Kh. Kopylov; S. A. Ivanov; T. E. Svetoch; R. Z. Shaikhutdinova; A. A. Kislichkina; A. G. Bogun; S. V. Dentovskaya (Инфекция и иммунитет, 2018)
.